2017
DOI: 10.1007/s11846-017-0229-0
|View full text |Cite
|
Sign up to set email alerts
|

Management innovation, pro-innovation organisational culture and enterprise performance: testing the mediation effect

Abstract: The interest in management innovation (MI) is growing and the conviction about its significant role in boosting an enterprise's competitive advantage and performance has recently gained ground. The studies on MI and its relationships with enterprise performance, which are relatively scarce in literature, indicate the complexity of these relationships. This inspired us to propose the management innovation construct and its operationalisation, which allowed for the empirical verification of the relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
1
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 67 publications
3
58
1
6
Order By: Relevance
“…The analysis showed that intellectual capital had no significant effect on the culture of innovation with a coefficient of 0.139 and t statistics of 1.759 so that hypothesis 1 was rejected as well as refuting the results of the research [9][10][11]. The relationship of innovation culture with business performance is significant with a coefficient of 0.536 and statistics 5.817 which means hypothesis 2 is accepted and in line with the results of the study [12][13], while the relationship between intellectual capital and business performance is significant with a coefficient of 0.459 with t statistics 5.104 which means hypothesis 3 is accepted so that it is in line with the research conducted [3][4][5].…”
supporting
confidence: 57%
See 1 more Smart Citation
“…The analysis showed that intellectual capital had no significant effect on the culture of innovation with a coefficient of 0.139 and t statistics of 1.759 so that hypothesis 1 was rejected as well as refuting the results of the research [9][10][11]. The relationship of innovation culture with business performance is significant with a coefficient of 0.536 and statistics 5.817 which means hypothesis 2 is accepted and in line with the results of the study [12][13], while the relationship between intellectual capital and business performance is significant with a coefficient of 0.459 with t statistics 5.104 which means hypothesis 3 is accepted so that it is in line with the research conducted [3][4][5].…”
supporting
confidence: 57%
“…Most researchers tend to focus on one problem, both intellectual capital [8], both only a few that offer a dual association of intellectual capital and performance, and a culture of innovation [9][10][11] or associations of organizational culture, performance and innovation culture [12]; [13].…”
mentioning
confidence: 99%
“…To perform sustainability practices in the current era of globalization, firms use different approaches. However, out of many approaches, MI has deemed a significant factor especially in emerging markets [64]. Due to the increasing importance of sustainability for business firms, managers have now focused the strategies (such as innovation, organization knowledge and learning) that can configure sustainability practices [65].…”
Section: Management Innovation and Organization Sustainabilitymentioning
confidence: 99%
“…Organizational culture (OC) can be defined as a set of assumptions that unite the norms and values, social ideals, or beliefs that are shared by the members of an organization (Schein, 1993). In this sense, OC can influence employee behavior and formal systems of control (Chang & Lin, 2007), guiding the way in which employees think, act, and respond to improvement and innovation actions (Hofstede, 1991;Hung et al, 2005;Kraśnicka et al, 2018;Lee et al, 2016). Sørensen (2002) suggests that a strong culture, in which standards and values are widely shared and deeply retained throughout the organization, improves the organization's performance because employees are committed to common goals.…”
Section: Organizational Culture (Oc)mentioning
confidence: 99%
“…Culture is also known to support innovation by generating a creative organizational climate (Büschgens et al, 2013;Naqshbandi et al, 2015) and influences organizational performance (Kraśnicka et al, 2018). Büschgens et al (2013) identified that the way in which a company directs its organizational culture can broaden its innovative posture, since innovative organizations may develop a culture of flexibility and external orientation.…”
Section: Organizational Culture (Oc)mentioning
confidence: 99%